2018
DOI: 10.1039/c8ra02958j
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of zirconium dioxides for the design of better oxygen-ion conductors using efficient algorithms beyond data mining

Abstract: It is important to find crystal structures with low formation (E v ) and migration-barrier (E m ) energies for oxygen vacancies for the development of fast oxygen-ion conductors. To identify crystal structures with lower E v and E m than those of ground-state ZrO 2 , we first reoptimize the crystal structures of various oxides reported in the database, and then directly construct them using an evolutionary algorithm. For efficient searching, we employ the linearized ridge regression model for E v using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Based on database decomposition, Lee et al suggested a new approach for mining association rules. Numerous useful systems have been created on this foundation [ 15 ]. According to Van Woezik and others, formative evaluation is more crucial to students' learning than summative evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…Based on database decomposition, Lee et al suggested a new approach for mining association rules. Numerous useful systems have been created on this foundation [ 15 ]. According to Van Woezik and others, formative evaluation is more crucial to students' learning than summative evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…We also computed E form and E mig as their low values are favorable for a higher σ O 40,41 . The E form values were computed using the conventional cubic cell (160 atoms with a lattice constant larger than 10 Å) 22 :where E (Ca 3 Fe 2 Ge 3 O 12 : D q ) is the energy of a supercell including a point defect ( V O or O i ), E (Ca 3 Fe 2 Ge 3 O 12 ) is the energy of a supercell of the perfect Ca 3 Fe 2 Ge 3 O 12 , n D is 1 (or −1), which corresponds to the interstitial defect (or vacancy), μ O is the chemical potential of an added (or removed) O, q is the charge of the point defect, E HOMO is the eigenvalue of the HOMO formed mainly by O 2 p , E Fermi is the Fermi level as a variable, and Δ E LZ is the correction term proposed by Lany and Zunger 42,43 to compensate the image charge interactions between supercells for the charged point defect.…”
Section: Methodsmentioning
confidence: 99%
“…We also computed E v and E m because their low values are favorable for achieving a higher σ O [31,32]. The E v values were computed using the supercell method [33] as follows:…”
Section: First-principles Calculationsmentioning
confidence: 99%